Designing interventions in local value chains for improved health and nutrition: Insights from Malawi - Donovan, Jason; Gelli, Aulo (Elsevier, 2019)
Despite the strong interest on the role of agri-food value chains in advancing health and nutrition goals, guidance on how to actually design and assess related development programming has only recently emerged. This paper begins with a brief review of research on nutrition-sensitive value chains in developing countries. It then presents the Value Chains and Nutrition framework for intervention design that explores food supply and demand conditions across a portfolio of local value chains that are relevant for improving nutrition outcomes. We explore the framework in a case study on rural Malawi. Available evidence highlights the dominance of maize in diets, but also the willingness of rural households to consume other nutritious foods (e.g. leafy greens, tree fruits, dried fish) during the year. Addressing the supply constraints (e.g. low productivity, seasonality) and demand constraints (e.g. low income, preference for maize) along local value chains will require carefully sequenced interventions within and across value chains. Strategies for achieving nutrition goals in this context will require stronger collaborative ties between NGOs, government agencies and the private sector and deeper learning among stakeholders than has typically been the case. We conclude with recommendations for future work on frameworks and tools for supporting the design of value chain interventions with potential to advance health and nutrition goals.